DESIGN OF INFORMATION SYSTEM ARCHIVING INCOME AND OUTGOING MAIL BASED ON THE WEB AT DISKOMINFO KABUPATEN BANDUNG - Johni S Pasaribu (Journal of International Conference Proceedings (JICP), 2019)
The archive is a recording of activities that must be managed properly and carefully. Management archive of incoming letters or outgoing letter at the Bandung District Diskominfo still managed manually, by collecting files relating to all activities at the Bandung District Diskominfo in one place and stored in a storage closet. Management of this kind causes the lack of rigor according to the classification and archiving based on the type and importance, consequently officer had difficulty in finding the necessary documents. One of the other problems that arise is the specially for incoming letters which must include a disposition sheet from the Head of Service, so if at any time the Head of Service is not in place, it will hamper the follow-up. And when making a report in the manual system, it must record the report of the incoming and outgoing mail. It required an information system archiving of incoming mails or outgoing mails web-based that can facilitate the work of. This information system is designed using the programming language PHP and uses an object-based modeling techniques to describe the analysis and design of the system. The results of this software can be used in the Bandung District Diskominfo environment so that the new system can make it easier to search, faster and secure file archives stored. The Service Head can be when not in place, further instructions for incoming mail are not hampered. Making Reports easier without having to re-record the data of incoming and outgoing mail.